CHARACTERIZATION OF ORGANIC ACIDS IN JUICES OF SOME PAKISTANI CITRUS SPECIES AND THEIR RETENTION DURING REFRIGERATED STORAGE - M. A. Randhawa; A. Rashid; M. Saeed; M. S. Javed; A. A. Khan; M. W. Sajid (Journal of Animal and Plant Sciences, 2014)
Organic acids play pivotal role in flavor and consumer acceptance of fruit beverages. Concentration of some organic acids in citrus juices was determined through HPLC and their retention during refrigerated storage was also evaluated. The concentration of organic acids were in the following pattern Citric Acid> Malic Acid> Ascorbic Acid> Tartaric Acid. Citric acid, malic acid, ascorbic acid and tartaric acid content ranged from 925.92 mg/100 mL (Kinnow) to 1323.25 mg/100 mL (Musambi), 9.67 mg/100 mL (Musambi) to 519.62 mg/100 mL (Kinnow), 36.38 mg/100 mL (red blood) to 51.43 mg/100 mL (Kinnow), 0.318 mg/100 mL (Musambi) to 0.825 mg/100 mL (Kinnow), respectively in different citrus species. Storage studies revealed that ascorbic acid losses were 11% to 15% and citric acid contents were decreased from 0.7% to 1.9% during refrigerated storage while malic acid contents increased 1% to 4% and tartaric acid content increased 2% to 4% thoroughout the storage period.
Keywords: Characterization; Organic acids; Citrus juices; Refrigerated storage